Preparation method of multi-channel Ni / CM ceramic catalytic membrane
By hydrothermally growing Ni-BTC on a multi-channel ceramic membrane substrate and calcining it to form a Ni/CM catalytic membrane, the problems of low active component loading and weak binding force in traditional catalytic membrane preparation are solved, and efficient catalytic performance is achieved. and cyclic stability.
Patent Information
- Application Number
- CN202411529545.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-10-30
AI Technical Summary
In the preparation of traditional catalytic films, there are problems such as low loading of active components and weak binding force, which leads to the easy inactivation of the catalytic film during use.
Ni-BTC is grown in situ on a multi-channel ceramic membrane substrate using a hydrothermal method, and a multi-channel Ni/CM ceramic catalytic membrane is formed through subsequent calcination to enhance the binding force between the active components and the membrane.
The loading capacity and binding force of active components on the membrane are increased, nickel nanoparticles with smaller particle size and better dispersion are formed, which significantly improves the catalytic performance and cycle stability of the catalytic membrane.
Smart Images

Figure CN119327462A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalytic film preparation, and relates to a method for preparing a multi-channel Ni / CM ceramic catalytic film. Background Art
[0002] p-Nitrophenol is an aromatic nitro compound and a persistent hazardous pollutant that is widely present in various industrial and agricultural wastewaters. Even trace amounts of p-nitrophenol can cause significant harm to human health and the natural environment. The common strategy for treating p-nitrophenol is to convert it into other components, such as p-aminophenol, at room temperature. p-Aminophenol is an essential intermediate in the pharmaceutical industry, and its toxicity is less than 1 / 500 of that of p-nitrophenol. In recent years, noble metals and their alloys (Pd, Au and Ag), transition metal oxides, hybrid materials, etc. have been applied to the catalytic reduction of p-nitrophenol. Although the catalytic activity of noble metal catalysts is high, the cost and scarcity of the materials still limit their application. At the same time, in order to improve the activity, the noble metals are usually loaded on fine-grained carriers. These powder catalysts are easily deactivated during use, and the catalyst recovery and reuse process is complicated and the recovery rate is low, resulting in increased production costs. Therefore, the development of efficient new catalytic materials for the reduction of p-nitrophenol has attracted much attention.
[0003] Catalytic membranes are a type of material that loads active components onto the surface or pores of porous membranes. The countless interconnected pores in the membrane can provide effective loading sites for active components and reaction molecules. Compared with traditional intermittent reactions, chemical reactions in the flow mode based on catalytic membranes occur in the membrane pores. Due to the shorter diffusion distance and thinner concentration boundary layer, mass transfer is more efficient. At the same time, in the reaction process involving catalytic membranes, the separation and recovery process of catalysts can be omitted, improving production efficiency and the service life of catalysts. MOFs, as a type of crystalline porous material composed of alternately connected metal ions or small metal clusters and organic ligands, has advantages such as high specific surface area and porous structure, and the pore structure is adjustable and easy to functionalize. These advantages make MOFs show great potential in the field of catalysis, providing rich resources and broad prospects for the development of new and efficient catalytic materials. However, the preparation of traditional catalytic membranes mostly adopts the impregnation method, which has the problems of low active component loading and weak binding force between active components and membrane substrate, resulting in the easy deactivation of catalytic membranes during later use. Summary of the invention
[0004] Aiming at the problems existing in the preparation of traditional catalytic membranes, the present invention proposes a novel method for preparing a multi-channel Ni / CM ceramic catalytic membrane.
[0005] In order to achieve the above object, the present invention is implemented by adopting the following technical solutions: A method for preparing a multi-channel Ni / CM ceramic catalytic membrane comprises the following steps.
[0006] Step 1: Add 1,3,5-benzenetricarboxylic acid into a ternary mixed solvent of deionized water, N,N-dimethylformamide and ethylene glycol, stir thoroughly to dissolve, and obtain a mixed solution A.
[0007] Step 2: Add nickel nitrate hexahydrate into mixed solution A, stir thoroughly to dissolve, and obtain mixed solution B.
[0008] Step 3: Immerse the pretreated ceramic membrane in the mixed solution B, conduct a hydrothermal reaction under sealed conditions, and cool to room temperature after the reaction. Take out the ceramic membrane and ultrasonically wash it with N,N-dimethylformamide and ethanol in turn, and vacuum dry it to obtain a multi-channel Ni-BTC / CM ceramic membrane.
[0009] Step 4: calcining the multi-channel Ni-BTC / CM ceramic membrane in a hydrogen-argon mixed atmosphere to obtain a multi-channel Ni / CM ceramic catalytic membrane.
[0010] Preferably, the concentration of 1,3,5-benzenetricarboxylic acid in the mixed solution A in step 1 is 0.02-0.03 mol / L; the concentration of nickel nitrate hexahydrate in the mixed solution B in step 2 is 0.035-0.065 mol / L.
[0011] Preferably, the pretreatment process of the ceramic membrane in step three is: placing the ceramic membrane in deionized water, boiling it for 4-6 hours, and after the boiling treatment, drying it at 90-100°C for at least 8 hours; the hydrothermal reaction temperature is 140-160°C, and the hydrothermal reaction time is 8-12 hours; the N,N-dimethylformamide ultrasonic washing time is 10-16 minutes, the ethanol ultrasonic washing time is 15-45 minutes, the vacuum drying temperature is 75-85°C, and the drying time is 10-14 hours.
[0012] Preferably, in step 4, the volume fraction of hydrogen in the hydrogen-argon mixed gas is 8-11%, the calcination temperature is 400-470°C, the heating rate is 3-8°C / min, and after heating to the calcination temperature, the calcination time is 2-4h.
[0013] The present invention proposes that the multi-channel Ni / CM ceramic catalytic membrane prepared by the above method is applied to the selective hydrogenation reduction of p-nitrophenol to prepare p-aminophenol.
[0014] The reaction process of the selective catalytic hydrogenation reduction of p-nitrophenol to prepare p-aminophenol can be intermittent or continuous. In the continuous reaction, the catalyst membrane remains in place, the reaction solution is continuously fed, and after the catalytic reaction of the catalyst membrane, the reaction product is continuously output. No catalyst separation is required during the entire catalytic reaction process. In the intermittent reaction, the catalyst membrane can be recycled and reused many times, and then the fresh reaction solution is added to the reactor and catalyzed by the recycled multi-channel Ni / CM ceramic catalyst membrane. The recycling method is: after the reaction is completed, the catalyst membrane is taken out and placed in deionized water to soak for 20-40 minutes, and it can be used directly without additional catalyst separation operation.
[0015] The present invention successfully loads Ni-BTC on the surface and pores of a multi-channel ceramic membrane substrate by changing the molar ratio of the organic ligand 1,3,5-benzenetricarboxylic acid to the metal source nickel nitrate hexahydrate, the hydrothermal temperature, the hydrothermal time and the calcination temperature, and forms nickel nanoparticles in situ on the surface and pores of the ceramic membrane by calcining in a reducing atmosphere, thereby successfully preparing an efficient nickel-based catalytic membrane. In a high-temperature hydrothermal system, due to the air pressure generated during the hydrothermal process, the precursor solution penetrates into the membrane pores under the action of pressure, and the confined growth of Ni-BTC in the membrane pores can be achieved due to the size limitation of the membrane pores themselves. Ni-BTC can not only interact with the membrane substrate by physical adsorption, but the nickel ions therein may also form coordination bonds with the oxygen atoms in the membrane, so that Ni-BTC is more stably loaded on the surface and pores of the membrane and is not easy to fall off. In addition, the deposition of Ni-BTC in the membrane causes the microstructure of the membrane surface to change, forming a specific interface layer. In addition, during the high-temperature calcination process, the specific interface layer formed on the surface of the precursor can migrate to the inside of the ceramic membrane substrate through surface diffusion. When the decomposition temperature of Ni-BTC on the membrane surface and in the pores is reached, the reductive hydrogen and carbon matrix simultaneously reduce the nickel ions in situ to nickel metal elements. Calcination in a reductive atmosphere makes the chemical bond between the catalyst and the ceramic membrane more solid, thereby enhancing the bonding force between the two, and because the dispersion of the membrane pores and the presence of a large number of hydroxyls can effectively avoid the migration of nickel nanoparticles, thereby ensuring the high dispersion of nickel nanoparticles with smaller particle size on the membrane. Therefore, the preparation technology of the nickel-based catalytic membrane adopted in the present invention not only improves the loading amount of the active component on the membrane, enhances the bonding force between the active component and the membrane, but also is more conducive to forming nickel nanoparticles with smaller particle size and better dispersion, thereby improving the catalytic performance of the catalytic membrane.
[0016] Compared with the prior art, the advantages and positive effects of the present invention are: 1. The present invention adopts a hydrothermal method to directly in-situ grow Ni-BTC on a multi-channel ceramic membrane substrate, and the Ni / CM catalytic membrane formed by subsequent calcination has good selective hydrogenation catalytic performance.
[0017] 2. The multi-channel Ni / CM ceramic catalytic membrane prepared by the present invention has active component Ni nanoparticles on the surface and in the pores, which greatly increases the loading amount of the active component and thus improves the catalytic efficiency.
[0018] 3. The multi-channel Ni / CM ceramic catalytic membrane prepared by the present invention has excellent cyclic stability, and the activity of the catalytic membrane remains stable after multiple cyclic reactions. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is the SEM image of the multi-channel Ni / CM ceramic catalytic membrane prepared in Example 1.
[0020] Figure 2 This is the XRD pattern of the multi-channel Ni / CM ceramic catalytic membrane prepared in Example 1.
[0021] Figure 3 These are the cyclic stability test results of the multi-channel Ni / CM ceramic catalytic membrane prepared in Example 1. DETAILED DESCRIPTION
[0022] In order to more clearly understand the above-mentioned purpose, features and advantages of the present invention, the present invention is further described below in conjunction with specific embodiments. It should be noted that the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.
[0023] In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways than those described herein. Therefore, the present invention is not limited to the specific embodiments of the following disclosure.
[0024] Example 1 This embodiment provides a specific preparation process of a multi-channel Ni / CM ceramic catalyst membrane.
[0025] (1) Preparation of Ni-BTC / CM membrane First, prepare 150mL of a mixed solvent of deionized water: N,N-dimethylformamide: ethylene glycol with a volume ratio of 5:10:3, stir and mix thoroughly, then add 0.00375mol of 1,3,5-benzenetricarboxylic acid, stir for 30min at a water bath temperature of 25℃, then add 0.0075mol of nickel nitrate hexahydrate, and continue stirring for 15min at a water bath temperature of 25℃, the stirring rate is 200rpm, and the raw material solution is prepared. Pour the raw material solution into a polytetrafluoroethylene liner with a stainless steel shell and a top cover, put into a multi-channel ceramic membrane (alumina, 19 channels, length 8cm, outer diameter 3cm, average pore size 1μm) that has been boiled for 5h and dried in a 95℃ oven for 12h, assemble the stainless steel shell of the hydrothermal autoclave with the liner and tighten the top cover to seal (other hydrothermal autoclaves that can achieve sealing can also be used), and then put the entire sealed hydrothermal autoclave into an oven preheated to 150℃ for hydrothermal reaction for 10h. After the reaction, the tube was naturally cooled to room temperature, the green Ni-BTC / CM membrane tube was taken out, and then the membrane tube was immersed in N,N-dimethylformamide for ultrasonic washing for 13 minutes, and then immersed in ethanol for ultrasonic washing for 30 minutes. After the ultrasonic washing was completed, it was taken out and vacuum dried at 80°C for 12 hours to obtain the Ni-BTC / CM membrane.
[0026] (2) Preparation of Ni / CM catalytic membrane The dried Ni-BTC / CM membrane was placed in a tube furnace, sealed, and evacuated. A hydrogen-argon mixture with a hydrogen volume concentration of 10% was introduced, and the temperature was raised from room temperature to 435°C at a heating rate of 5°C / min, and maintained at this temperature for 3 hours. After the calcination, it was naturally cooled to room temperature to obtain a black Ni / CM catalytic membrane.
[0027] The performance of Ni / CM catalytic membrane was verified by flow-through membrane reactor using the selective catalytic hydrogenation reduction of p-nitrophenol to p-aminophenol as a model reaction. Prepare 240mL of p-nitrophenol solution with a concentration of 0.03mol / L (the solvent is a mixed solvent of ethanol and water with a volume ratio of 1:5), and take 0.4mL of reaction solution as the original sample for standby use as a control group. Add 2.6g of NaBH4 to the remaining reaction solution and stir magnetically at room temperature for 3-7min until the solid is completely dissolved. While preparing the above reaction solution, fix the Ni / CM catalytic membrane in the membrane assembly, open the constant temperature water bath and set the target temperature to 35℃, open the circulation, so that the constant temperature water enters the jacket of the raw material tank and the jacket of the membrane assembly (the raw material tank and the membrane assembly are set separately and connected by pipelines) to preheat the system. After preheating ends, the above-mentioned reaction solution is poured into the raw material tank, and the reaction solution is transported to the membrane reactor at a rate of 1.8L / h using a peristaltic pump to control the reaction solution. When the reaction solution circulates back to the raw material tank, the timing is started, and 0.4mL of reaction solution is taken every 5min, and liquid chromatography is performed on its composition. After the reaction ends, the catalytic membrane is disassembled and soaked and cleaned for subsequent use. High performance liquid chromatograph is used to carry out component analysis of each sample to be tested, and reactant conversion and product selectivity are calculated according to a standard curve. After testing, in the present embodiment, when the reaction is carried out for 25min, the conversion rate of p-nitrophenol is 95.1%, and the selectivity of p-aminophenol is 100%.
[0028] Figure 1 This is a SEM image of the multi-channel Ni / CM ceramic catalytic membrane in Example 1. It can be seen from the image that there are particles on the ceramic membrane substrate, indicating that the active components are successfully loaded on the multi-channel ceramic membrane.
[0029] Figure 2 This is the XRD pattern of the powdered Ni / C catalyst corresponding to the multi-channel Ni / CM ceramic membrane in Example 1 (due to the strong intensity of the alumina diffraction peak of the ceramic membrane itself, which will cover the diffraction peak of Ni, the Ni / C catalyst prepared by calcining the Ni-BTC powder remaining in the kettle after the hydrothermal reaction was completed was used for testing). The diffraction peak at 2θ of 26° belongs to the (002) crystal plane of graphite carbon, the diffraction peaks at 2θ of 44.5°, 51.8° and 76.4° respectively belong to the (111), (200) and (220) crystal planes of Ni, and the weak diffraction peak at 2θ of 62.6° belongs to the (220) crystal plane of NiO.
[0030] Example 2 This example provides a preparation process of a Ni / CM catalyst membrane and an application of selective catalytic hydrogenation reduction of p-nitrophenol to prepare p-aminophenol. Where not specifically described in this example, the same procedures as in Example 1 are used.
[0031] (1) Preparation of Ni-BTC / CM membrane First, prepare 150mL of a mixed solvent of deionized water: N,N-dimethylformamide: ethylene glycol with a volume ratio of 5:10:3, stir and mix thoroughly, then add 0.003mol of 1,3,5-benzenetricarboxylic acid, stir for 35min at a water bath temperature of 20℃, then add 0.00525mol of nickel nitrate hexahydrate, and continue stirring for 20min at a water bath temperature of 20℃, the stirring rate is 200rpm, and the raw material solution is prepared. Pour the raw material solution into a polytetrafluoroethylene liner with a stainless steel shell and a top cover, put into a multi-channel ceramic membrane (zirconia, 19 channels, length 8cm, outer diameter 3cm, average pore size 1μm) that has been boiled for 4h and dried in a 90℃ oven for 12h, assemble the stainless steel shell of the hydrothermal autoclave with the liner and tighten the top cover to seal (other hydrothermal autoclaves that can achieve sealing can also be used), and then put the entire sealed hydrothermal autoclave into an oven preheated to 140℃ for hydrothermal reaction for 12h. After the reaction, the tube was naturally cooled to room temperature, the green Ni-BTC / CM membrane tube was taken out, and then the membrane tube was immersed in N,N-dimethylformamide for ultrasonic washing for 10 minutes, and then immersed in ethanol for ultrasonic washing for 15 minutes. After the ultrasonic washing was completed, it was taken out and vacuum dried at 75°C for 14 hours to obtain the Ni-BTC / CM membrane.
[0032] (2) Preparation of Ni / CM catalytic membrane The dried Ni-BTC / CM membrane was placed in a tubular furnace, sealed, and evacuated. A hydrogen-argon mixture with a hydrogen volume concentration of 11% was introduced, and the temperature was increased from room temperature to 400°C at a heating rate of 3°C / min and maintained at this temperature for 4 hours. After the calcination, it was naturally cooled to room temperature to obtain a black Ni / CM catalytic membrane.
[0033] The Ni / CM catalyst membrane prepared in this example was used to catalyze the hydrogenation reduction of p-nitrophenol to prepare p-aminophenol, and the reaction materials were the same as those in Example 1. When the reaction was carried out for 25 minutes, the conversion rate of p-nitrophenol was 90.5%, and the selectivity of p-aminophenol was 100%.
[0034] Example 3 This example provides a preparation process of a Ni / CM catalyst membrane and an application of selective catalytic hydrogenation reduction of p-nitrophenol to prepare p-aminophenol. Where not specifically described in this example, the same procedures as in Example 1 are used.
[0035] (1) Preparation of Ni-BTC / CM membrane First, prepare 150mL of a mixed solvent of deionized water: N,N-dimethylformamide: ethylene glycol with a volume ratio of 5:10:3, stir and mix thoroughly, then add 0.0045mol of 1,3,5-benzenetricarboxylic acid, stir at 30℃ water bath temperature for 25min, then add 0.00975mol of nickel nitrate hexahydrate, and continue stirring at 30℃ water bath temperature for 10min, the above stirring rate is 200rpm, and the raw material solution is prepared. Pour the raw material solution into a polytetrafluoroethylene liner with a stainless steel shell and a top cover, put into a multi-channel ceramic membrane (alumina, 37 channels, length 8cm, outer diameter 3cm, average pore size 1μm) that has been boiled for 6h and dried in a 100℃ oven for 12h, assemble the stainless steel shell of the hydrothermal autoclave with the liner and tighten the top cover to seal (other hydrothermal autoclaves that can achieve sealing can also be used), and then put the entire sealed hydrothermal autoclave into an oven preheated to 160℃ for hydrothermal reaction for 8h. After the reaction is completed, the green Ni-BTC / CM membrane tube is taken out after naturally cooling to room temperature. The membrane tube is then immersed in N,N-dimethylformamide for ultrasonic washing for 16 minutes and then immersed in ethanol for ultrasonic washing for 45 minutes. After the ultrasonic washing is completed, it is taken out and vacuum dried at 85°C for 10 hours to obtain a Ni-BTC / CM membrane.
[0036] (2) Preparation of Ni / CM catalytic membrane The dried Ni-BTC / CM membrane was placed in a tube furnace, sealed, and evacuated. A hydrogen-argon mixture with a hydrogen volume concentration of 8% was introduced, and the temperature was raised from room temperature to 470°C at a heating rate of 7°C / min, and maintained at this temperature for 2 hours. After the calcination, it was naturally cooled to room temperature to obtain a black Ni / CM catalytic membrane.
[0037] After testing, it was found that when the membrane tube prepared in this example was used for catalysis and the reaction was carried out for 25 minutes, the conversion rate of p-nitrophenol was 86.3%, and the selectivity of p-aminophenol was 100%.
[0038] Example 4 This example uses the catalyst membrane in Example 1 for multiple cycles to verify the cycle stability of the catalyst membrane. After each reaction, the membrane tube is taken out and soaked in deionized water for 30 minutes before it can be used again. Figure 3 As shown in the figure, when each reaction was carried out for 25 minutes, except for the first reaction, the conversion rate of p-nitrophenol was slightly lower, and the conversion rates of the other six reactions all reached 100% (after the first reaction, part of the nickel oxide was reduced to zero-valent nickel by sodium borohydride, and the catalytic membrane was very stable, so the catalytic activity of the recycled catalytic membrane was higher than that of the fresh catalytic membrane). After 7 cycles of reaction, there was no obvious deactivation of the catalytic membrane, and the stability was good.
[0039] Comparative Example 1 The difference between this comparative example and Example 1 is that the hydrothermal reaction temperature during the preparation of the catalytic membrane is different, so as to verify the influence of the hydrothermal temperature on the performance of the catalytic membrane within the protection scope of the present invention.
[0040] (1) Preparation of Ni-BTC / CM membrane First, prepare 150mL of a mixed solvent of deionized water: N,N-dimethylformamide: ethylene glycol with a volume ratio of 5:10:3, stir and mix thoroughly, then add 0.00375mol of 1,3,5-benzenetricarboxylic acid, stir for 30min at 25℃ water bath temperature, then add 0.0075mol of nickel nitrate hexahydrate, and continue stirring for 15min at 25℃ water bath temperature, the stirring rate is 200rpm, and the raw material solution is prepared. Pour the raw material solution into a polytetrafluoroethylene liner with a stainless steel shell and a top cover, put into a multi-channel ceramic membrane (alumina, 19 channels, length 8cm, diameter 3cm, average pore size 1um) that has been boiled for 5h and dried in a 95℃ oven for 12h, assemble the stainless steel shell of the hydrothermal autoclave with the liner and tighten the top cover to seal (other hydrothermal autoclaves that can achieve sealing can also be used), and then put the entire sealed hydrothermal autoclave into an oven preheated to 110℃ for hydrothermal reaction for 10h. After the reaction, the green Ni-BTC / CM membrane tube was taken out after naturally cooling to room temperature. The membrane tube was then immersed in N,N-dimethylformamide for ultrasonic washing for 13 minutes and then immersed in ethanol for ultrasonic washing for 30 minutes. After the ultrasonic washing was completed, the membrane tube was taken out and vacuum dried at 80°C for 12 hours to obtain a Ni-BTC / CM membrane.
[0041] (2) Preparation of Ni / CM catalytic membrane The dried Ni-BTC / CM membrane was placed in a tube furnace, sealed, and evacuated. A hydrogen-argon mixture with a hydrogen volume concentration of 10% was introduced, and the temperature was raised from room temperature to 435°C at a heating rate of 5°C / min, and maintained at this temperature for 3 hours. After the calcination, it was naturally cooled to room temperature to obtain a black Ni / CM catalytic membrane.
[0042] After testing, it was found that when the reaction was carried out for 25 minutes, the conversion rate of p-nitrophenol was 37.9% and the selectivity of p-aminophenol was 100%.
[0043] Comparative Example 2 The difference between this comparative example and Example 1 is that the calcination temperature is different, so as to verify the influence of the calcination temperature on the performance of the catalytic membrane within the protection scope of the present invention.
[0044] (1) Preparation of Ni-BTC / CM membrane First, prepare 150mL of a mixed solvent of deionized water: N,N-dimethylformamide: ethylene glycol with a volume ratio of 5:10:3, stir and mix thoroughly, then add 0.00375mol of 1,3,5-benzenetricarboxylic acid, stir for 30min at a water bath temperature of 25℃, then add 0.0075mol of nickel nitrate hexahydrate, and continue stirring for 15min at a water bath temperature of 25℃, the stirring rate is 200rpm, and the raw material solution is prepared. Pour the raw material solution into a polytetrafluoroethylene liner with a stainless steel shell and a top cover, put into a multi-channel ceramic membrane (alumina, 19 channels, length 8cm, diameter 3cm, average pore size 1um) that has been boiled for 5h and dried in a 95℃ oven for 12h, assemble the stainless steel shell of the hydrothermal autoclave with the liner and tighten the top cover to seal (other hydrothermal autoclaves that can achieve sealing can also be used), and then put the entire sealed hydrothermal autoclave into an oven preheated to 150℃ for hydrothermal reaction for 10h. After the reaction, the green Ni-BTC / CM membrane tube was taken out after naturally cooling to room temperature. The membrane tube was then immersed in N,N-dimethylformamide for ultrasonic washing for 13 minutes and then immersed in ethanol for ultrasonic washing for 30 minutes. After the ultrasonic washing was completed, the membrane tube was taken out and vacuum dried at 80°C for 12 hours to obtain a Ni-BTC / CM membrane.
[0045] (2) Preparation of Ni / CM catalytic membrane The dried Ni-BTC / CM membrane was placed in a tube furnace, sealed, and evacuated. A hydrogen-argon mixture with a hydrogen volume concentration of 10% was introduced, and the temperature was raised from room temperature to 335°C at a heating rate of 5°C / min, and maintained at this temperature for 3 hours. After the calcination, it was naturally cooled to room temperature to obtain a black Ni / CM catalytic membrane.
[0046] After testing, it was found that when the reaction was carried out for 25 minutes, the conversion rate of p-nitrophenol was 21.2% and the selectivity of p-aminophenol was 100%.
[0047] Comparative Example 3 The difference between this comparative example and Example 1 is that the volume concentration of hydrogen in the calcination atmosphere is different, so as to verify the influence of the volume concentration of hydrogen on the performance of the catalytic membrane within the protection scope of the present invention.
[0048] (1) Preparation of Ni-BTC / CM membrane First, prepare 150mL of a mixed solvent of deionized water: N,N-dimethylformamide: ethylene glycol with a volume ratio of 5:10:3, stir and mix thoroughly, then add 0.00375mol of 1,3,5-benzenetricarboxylic acid, stir for 30min at a water bath temperature of 25℃, then add 0.0075mol of nickel nitrate hexahydrate, and continue stirring for 15min at a water bath temperature of 25℃, the stirring rate is 200rpm, and the raw material solution is prepared. Pour the raw material solution into a polytetrafluoroethylene liner with a stainless steel shell and a top cover, put into a multi-channel ceramic membrane (alumina, 19 channels, length 8cm, diameter 3cm, average pore size 1um) that has been boiled for 5h and dried in a 95℃ oven for 12h, assemble the stainless steel shell of the hydrothermal autoclave with the liner and tighten the top cover to seal (other hydrothermal autoclaves that can achieve sealing can also be used), and then put the entire sealed hydrothermal autoclave into an oven preheated to 150℃ for hydrothermal reaction for 10h. After the reaction, the green Ni-BTC / CM membrane tube was taken out after naturally cooling to room temperature. The membrane tube was then immersed in N,N-dimethylformamide for ultrasonic washing for 13 minutes and then immersed in ethanol for ultrasonic washing for 30 minutes. After the ultrasonic washing was completed, the membrane tube was taken out and vacuum dried at 80°C for 12 hours to obtain a Ni-BTC / CM membrane.
[0049] (2) Preparation of Ni / CM catalytic membrane The dried Ni-BTC / CM membrane was placed in a tube furnace, sealed, and evacuated. A hydrogen-argon mixture with a hydrogen volume concentration of 40% was introduced, and the temperature was raised from room temperature to 435°C at a heating rate of 5°C / min, and maintained at this temperature for 3 hours. After the calcination, it was naturally cooled to room temperature to obtain a black Ni / CM catalytic membrane.
[0050] After testing, it was found that when the reaction was carried out for 25 minutes, the conversion rate of p-nitrophenol was 34.3% and the selectivity of p-aminophenol was 100%.
[0051] Comparative Example 4 The difference between this comparative example and Example 1 is that the multichannel ceramic membrane substrate used in the preparation process is not boiled, and the remaining steps are consistent with Example 1. When the reaction is carried out for 25 minutes, the conversion rate of p-nitrophenol is 69.8%, and the selectivity of p-aminophenol is 100%. It can be seen that whether the membrane substrate used for the preparation of the catalytic membrane is boiled has a significant effect on its catalytic performance. By boiling, excess impurities on the membrane surface and in the pores can be removed, which is conducive to the growth of Ni-BTC on the membrane, thereby increasing the loading amount of the active component on the membrane.
[0052] The above description is only a preferred embodiment of the present invention and does not limit the present invention in other forms. Any technician familiar with the profession may use the technical content disclosed above to change or modify it into an equivalent embodiment with equivalent changes and apply it to other fields. However, any simple modification, equivalent change and modification made to the above embodiment based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a multi-channel Ni / CM ceramic catalyst membrane, characterized in that: Here are the steps: Step 1: Add 1,3,5-benzenetricarboxylic acid into a ternary mixed solvent of deionized water, N,N-dimethylformamide, and ethylene glycol, and stir thoroughly to dissolve to obtain a mixed solution A; Step 2: Add nickel nitrate hexahydrate into mixed solution A, stir thoroughly to dissolve, and obtain mixed solution B; Step 3: Immerse the pretreated ceramic membrane in the mixed solution B, conduct a hydrothermal reaction under a sealed condition, and cool to room temperature after the reaction is completed; take out the ceramic membrane and wash it with N,N-dimethylformamide and ethanol ultrasonically in sequence, and vacuum dry it to obtain a multi-channel Ni-BTC / CM ceramic membrane; Step 4: calcining the multi-channel Ni-BTC / CM ceramic membrane in a hydrogen-argon mixed atmosphere to obtain a multi-channel Ni / CM ceramic catalytic membrane.
2. The method for preparing the multi-channel Ni / CM ceramic catalyst membrane according to claim 1, characterized in that: The concentration of 1,3,5-benzenetricarboxylic acid in the mixed solution A of step 1 is 0.02-0.03 mol / L; the concentration of nickel nitrate hexahydrate in the mixed solution B of step 2 is 0.035-0.065 mol / L.
3. The method for preparing the multi-channel Ni / CM ceramic catalyst membrane according to claim 1, characterized in that: The pretreatment process of the ceramic membrane in step three is: placing the ceramic membrane in deionized water, boiling it for 4-6 hours, and drying it at 90-100°C after the boiling treatment, and the drying time is at least 8 hours; the hydrothermal reaction temperature is 140-160°C, and the hydrothermal reaction time is 8-12 hours; the N,N-dimethylformamide ultrasonic washing time is 10-16 minutes, the ethanol ultrasonic washing time is 15-45 minutes, the vacuum drying temperature is 75-85°C, and the drying time is 10-14 hours.
4. The method for preparing the multi-channel Ni / CM ceramic catalyst membrane according to claim 1, characterized in that: In step 4, the volume fraction of hydrogen in the hydrogen-argon mixed gas is 8-11%, the calcination temperature is 400-470° C., and the calcination time is 2-4 hours.
5. The multi-channel Ni / CM ceramic catalytic membrane prepared by any one of the methods of claims 1 to 4 is used in the selective hydrogenation reduction of p-nitrophenol to prepare p-aminophenol.
6. The use according to claim 5, characterized in that: The reaction process of preparing p-aminophenol by selective catalytic hydrogenation reduction of p-nitrophenol is intermittent or continuous.
7. The use according to claim 6, characterized in that: The recycled multi-channel Ni / CM ceramic catalytic membrane is used for catalysis, and the recycling method is: after the reaction is completed, the catalytic membrane is taken out and immersed in deionized water for 20-40 minutes.
Citation Information
Patent Citations
Simple preparation method of Co / CM ceramic catalytic membrane
CN113289666A
Carbon-coated nickel nano composite material as well as preparation method and application thereof
CN115121252A
Preparation method of multi-channel Co / CM ceramic catalytic membrane
CN117160510A
Preparation method and application of Ni / C catalyst
CN117414834A
Cited By
Preparation method of novel multichannel Ni / CM ceramic catalytic membrane
CN120243027A
A method for preparing a multi-channel Ni / CM ceramic catalytic membrane
CN120243027B